2019
DOI: 10.3390/ani9110986
|View full text |Cite
|
Sign up to set email alerts
|

The Facilitating Effect of Tartary Buckwheat Flavonoids and Lactobacillus plantarum on the Growth Performance, Nutrient Digestibility, Antioxidant Capacity, and Fecal Microbiota of Weaned Piglets

Abstract: Simple SummaryThere has been a growing interest in the use of flavonoids and probiotics as alternatives of antibiotics in livestock production and as natural products for human health benefit. The effect of tartary buckwheat flavonoid supplementation in the diet has not been clearly investigated. The supplementation of tartary buckwheat flavonoids or Lactobacillus plantarum improved the growth performance, nutrient digestibility, and antioxidant capacity of weaned piglets. In combination, they exhibited a syne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 51 publications
1
18
0
2
Order By: Relevance
“…One week after weaning, there is a decrease of SOD and GSH-Px activities as well as an increase of MDA, reflecting an imbalanced redox status during this stage (58). Under this circumstance, an improved antioxidant capability of weaned piglets is observed after the addition of L. plantarum by promoting of SOD, CAT, and GSH-Px activities (62). From a practical perspective, we aim to explore the mode of action of L. salivarius in ameliorating oxidative issues occurring in weaned piglets.…”
Section: Discussionmentioning
confidence: 95%
“…One week after weaning, there is a decrease of SOD and GSH-Px activities as well as an increase of MDA, reflecting an imbalanced redox status during this stage (58). Under this circumstance, an improved antioxidant capability of weaned piglets is observed after the addition of L. plantarum by promoting of SOD, CAT, and GSH-Px activities (62). From a practical perspective, we aim to explore the mode of action of L. salivarius in ameliorating oxidative issues occurring in weaned piglets.…”
Section: Discussionmentioning
confidence: 95%
“…Different strains of L. plantarum have shown strong acid resistance and bile resistance [ 19 ] and can be found in a variety of environmental niches such as dairy, vegetables, and mammal gastrointestinal tracts, as well as being used in human food, aquaculture, and livestock feed as probiotics [ 20 , 21 , 22 ]. A previous study also indicates that L. plantarum has a beneficial effect on pigs [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 93%
“…Feeding the Lactobacillus amylovorus strain, which is dominant in the pre-weaning pig microbial community, could help in maintaining its presence in post-feeding and contributing to protecting the post-weaning piglets from E. coli F4 infection [46]. In agreement with Konstantinov et al [46], another lactic acid bacteria (LAB), Lactobacillus plantarum, has shown promising results, contributing to increasing the level of recognized beneficial bacteria, including bacteria belonging to the Bifidobacteriaceae family [124] and the genera Lactobacillus and Mitsuokella [125,126]. More recently, attention to other bacteria, in addition to LAB bacteria, has increased and, of them, Bacillus spp.…”
Section: Post-weaning Dietmentioning
confidence: 68%